الشرط الجزائي ما بين العقوبة و التعويض الإتفاقي في المعاملات المالية المعاصرة - مصطفى عثمان عبدالله عبدالكريم; د. محمد عمار اسحق عبدالرحمن (White Nile Journal for Studies and Research, 2023)
This study aimed to examine the provisions of the clause in some of the Contemporary Transactions between the death penalty in the case of a breach that occurs in the contracts which the consequent mn responsibility Streptococcus or a result of negligence and shortening one of the parties to the contract , which follows that tort as the researcher Ray Sharia laws and contracts and reached to the following results clause in some contracts gives decade -plus commitment than making party , which is located on his shoulder this condition diligence to carry out its tasks in time and the right place . clause may be a penalty if they do not abide by one of the parties which result in the other party agreed compensation law.